Partnerships for leadership preparation and development : facilitators, barriers and models for change - Kochan, Frances K.; Reames, Ellen H.; Griggs, Dana M. (Dimensions of leadership and institutional success : exploring connections and partnerships., 2020)
"There is a large body of research that supports the reality that school leaders make a significant contribution to the success of schools and the students in them. Additionally, there is strong agreement among and between researchers and state and national educational leadership associations that educational leadership preparation and development should be created and implemented within university/school partnerships. Although institutions engage in forming university/school partnerships for varied reasons, research on the extent to which these partnerships exist; their organizational structures and processes; their implementation and effectiveness; and elements that foster and hinder their success is limited. Perhaps more importantly, there is not a widely accepted, research-based model of such partnerships that practitioners and researchers can use to guide the development and assessment of these partnership endeavors and upon which they can conduct effective research. This book seeks to fill these gaps. It presents the purposes, processes, practices and outcomes of eleven university/school partnerships focused on school leadership preparation and/or development. Each chapter presents an overview of the partnership, elements that fostered and hindered partnership success, and lessons learned. The book concludes with a chapter that summarizes findings across all chapters and presents a school/university partnership model that can be used by those interested in forming, improving or researcher similar partnership endeavors. There are no similar resources available in the field. Thus, this book makes an important contribution to the literature and to the world of practice and research"--